1999
DOI: 10.1016/s0006-3223(98)00255-8
|View full text |Cite
|
Sign up to set email alerts
|

Daily rhythm of serum melatonin levels and effect of light exposure in patients with dementia of the Alzheimer’s type

Abstract: The high levels of melatonin in the daytime associated with a lack of response to light exposure in AD patients may be due to the neurodegenerative process of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
1
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(71 citation statements)
references
References 28 publications
0
69
1
1
Order By: Relevance
“…Dementia patients have been noted to have abnormalities in their rhythms of melatonin secretion. 47,48 This dysfunction has been noted not only in patients with clinical diagnosis of AD, 9 but confirmed after postmortem analysis. 49 Light therapy, given after the temperature nadir, may also be an appropriate treatment.…”
Section: Commentmentioning
confidence: 56%
“…Dementia patients have been noted to have abnormalities in their rhythms of melatonin secretion. 47,48 This dysfunction has been noted not only in patients with clinical diagnosis of AD, 9 but confirmed after postmortem analysis. 49 Light therapy, given after the temperature nadir, may also be an appropriate treatment.…”
Section: Commentmentioning
confidence: 56%
“…Studies of melatonin levels in AD patients reveal that they are lower in AD patients compared to age matched controls [73][74][75][76]. Decreased CSF melatonin levels in AD patients were attributed to decreased melatonin production rather than to diluting effects of CSF.…”
Section: Melatonin Levels In Alzheimer's Diseasementioning
confidence: 99%
“…A number of studies have revealed that melatonin levels are lower in AD patients as compared to age-matched control subjects (Mishima et al 1999 ;Skene et al 1990 ;Ohashi et al 1999 ;Liu et al 1999 ). The decreased CSF melatonin levels of AD patients were attributed to a decreased melatonin production.…”
Section: Clinical Aspects Of Melatonin Application In Admentioning
confidence: 99%